Pembuatan Video Polusi Sampah Plastik Berbasis Iklan Layanan Masyarakat Menggunakan Teknik Frame Cutting Points Dan Voice Over - Hafid Pradana; Anton Topadang; Agusdi Syafrizal (JURNAL VOKASI TEKNIK, 2025)
The unchecked growth of plastic consumption has caused problems among society, such as polluting soil and water, as well as environmental damage. Plastic pollution can also negatively affect human health, through microplastics entering the food chain. In an effort to increase public awareness of the negative impacts of plastic waste pollution, the creation of a Public Service Announcement video is needed to help people realise the dangers of plastic waste pollution and also to reduce plastic consumption. This research aims to produce a video that is effective in providing insight into plastic waste pollution and encouraging action to reduce plastic waste pollution by using Frame Cutting Points and Voice over techniques. The use of Frame Cutting Points Technique can provide a strong visual effect and attract the attention of the audience, while the use of Voice Over aims to strengthen the message conveyed through clear narration. In making a Public Service Announcement video using the Frame Cutting Points technique supported by Voice Over, the video making process with pre-production, production and post-production stages is applied as the method of choice in video making. The research produced a Public Service Announcement video using the Frame Cutting Points technique and Voice Over with a duration of 2 minutes 45 seconds.